INHIBITION OF METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) BIOFILM: THE ESSENTIAL ROLE AND POTENTIAL USAGE OF BACTERIOCINS - Febrianti, Tati; Conny Riana Tjampakasari (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: The potential of Methicillin-Resistant Staphylococcus aureus (MRSA) to develop biofilms and its resistance to antibiotics become major worldwide issue. Complementary anti-microbial strategies have been used recently, in particular for the treatment of MRSA biofilm-associated resistance. Purpose: To review the potential, essential role, and mechanism of bacteriocin that can inhibit MRSA biofilms. The review was conducted by searching and analyzing published articles from Elsevier, ProQuest and PubMed database. Review: Globally, the incidence of MRSA in 85 countries based on WHO surveillance reaches more than 20%. Biofilm, as one of the virulence factors of MRSA, can result in the failure of antibiotic therapy. According to reports, bacteriocins, such as peptides synthesized by Gram-negative and Gram-positive bacteria, have antimicrobial activity that has the potential to inhibit antibiotic-resistant pathogens and biofilms formed by MRSA. Result: The bacteriostatic and bactericidal activity of bacteriocins against MRSA has been shown through research across several countries on the usage of bacteriocins, which was isolated from different types of bacteria against MRSA biofilms. Bacteriocins contribute to the inhibition of MRSA biofilms by inhibiting the synthesis of cell walls, leading to pores in the cytoplasmic membranes of bacterial cells, interrupting the synthesis of extracellular membranes, disrupting cell membranes, and reducing the number of planktonic cells within MRSA biofilms. Conclusion: Bacteriocins have an effective mechanism for treating MRSA biofilms with low toxicity and risk of resistance, hence they are safe to be developed as complementary components to antibiotics in an effort to treat MRSA biofilms.